Postmastectomy Radiotherapy After Neoadjuvant Chemotherapy in cT1-2N+ Breast Cancer Patients: A Single Center Experience and Review of Current Literature - Luo, Meng; Chen, Huihui; Deng, Hao; Jin, Yao; Wang, Gui; Zhang, Kun; Ma, Hong; Chen, Yiding; Zhang, Suzhan; Zhou, Jiaojiao (Frontiers in Oncology, 2022)
Purpose: Postmastectomy radiotherapy (PMRT) after neoadjuvant chemotherapy (NAC) in breast cancer patients with initial clinical stage cT1-2N+, especially for those who achieved ypT1-2N0, is still controversial. This study was to evaluate the survival prognosis of cT1-2N+ patients after NAC with or without PMRT, and to discuss the selection of patients who may omit PMRT. Patients and Methods: From January 2005 to December 2017, 3055 female breast cancer patients underwent mastectomy in our medical center, among whom 215 patients of cT1-2N+ stage, receiving NAC with or without PMRT were finally analyzed. The median follow-up duration was 72.6 months. The primary endpoint was disease-free survival (DFS), and secondary endpoint was overall survival (OS). Comparison was conducted between PMRT and non-PMRT subgroups. Results: Of the 215 eligible patients, 35.8% (77/215) cT1-2N+ patients achieved ypT0-2N0 after NAC while 64.2% (138/215) of the patients remained nodal positive (ypT0-2N+). The 5-year DFS of ypT0-2N0 non-PMRT was 79.5% (95% confidence interval [CI] 63.4-95.6%). No statistically significant difference was observed between the ypT0-2N0 PMRT and non-PMRT subgroups for the 5-year DFS (78.5% vs 79.5%, p = 0.673) and OS (88.8% vs 90.8%, p = 0.721). The 5-years DFS didn’t obviously differ between the ypT0-2N0 non-PMRT subgroup and cT1-2N0 subgroup (79.5% vs 93.3%, p = 0.070). By using Cox regression model in multivariate analyses of prognosis in ypT0-2N+ PMRT subgroup, HER2 overexpression and triple-negative breast cancer were significantly poor predictors of DFS and OS, while ypN stage was significant independent predictors of OS. Conclusion: An excellent response to NAC (ypT0-2N0) indicates a sufficiently favorable prognosis, and PMRT might be omitted for cT1-2N+ breast cancer patients with ypT0-2N0 after NAC.